1960
DOI: 10.1152/jappl.1960.15.3.503
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium metabolism in human beings: studies with Mg28

Abstract: Mg28 was used to explore the kinetics of magnesium distribution in 9 normal individuals and in 16 patients with various diseases. When Mg28 was given in 12–30 mEq of stable magnesium intravenously, plasma disappearance was rapid within the first several hours. In normal subjects a mean of 19.8% of the injected radioactivity was accounted for in the urine within 24 hours. Fecal excretion was negligible, although equilibration of Mg28 in bile occurred within 18 hours. The specific activities of plasma and urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
2

Year Published

1966
1966
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 0 publications
3
16
0
2
Order By: Relevance
“…There are minimal previous data regarding Mg kinetics in humans (7,8,12‐14) . The Mg exchangeable pool size (Mg comp ) reported in this study averaged 49 mg/kg, which is similar to previous results in adults (7,17) .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There are minimal previous data regarding Mg kinetics in humans (7,8,12‐14) . The Mg exchangeable pool size (Mg comp ) reported in this study averaged 49 mg/kg, which is similar to previous results in adults (7,17) .…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies using radioactive tracers have shown that Mg distribution occurs throughout the extracellular fluid during the initial hours after infusion, with subsequent distribution to separate compartments segregated from the extracellular fluid. Some component of the exchangeable Mg probably includes bone, although the exact size of this contribution is not readily measured (7,17,19) . We found evidence that this bone component is small by the ratio of Mg comp /Ca comp .…”
Section: Discussionmentioning
confidence: 72%
“…This is shown in figure 4 for LiCl targets ranging in thickness from 2 g/cm 2 to 32 g/cm 2 . It is clear that, regardless of the target thickness, the highest yield is always obtained with the highest incident proton energy.…”
Section: Fig 2 Excitation Function Ofmentioning
confidence: 89%
“…Since its introduction circa 1952 as a radiotracer in biochemical studies [1], 28 Mg found wide application in the study of absorption, retention and excretion in metabolic processes in animals and humans [2][3][4]. Magnesium is the second most abundant soft tissue intracellular cation in vertebrates and an essential nutrient for all living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Only 23% of MgTB (15 mmol kg-') exchanges with administered Mg isotope after 120 h and most of this is in tissues other than muscle or bone [31,54,55]. Given the relatively large variation from subject to subject, the short half-life (21.4 [4,47,56].…”
Section: Total Body Magnesiummentioning
confidence: 99%